Theoakgates / Norfazillah Ahmad ... [et al.] - Ahmad, Norfazillah; Mohamad Shahlan, Asma Zulaikha; Ahmad Zamri, Iklima Husna; Ibrahim, Nurulhuda (2024)
Students often get the stress of university life and have nowhere to “run away” when things get out of their control. Despite wanting to take their time to clear their mind out, they still need to be committed to their course assignments and tasks as their future depends on it. An idea of a student hub in the university compound can hopefully ease these problems. Not only can it be a place for them to relax or clear their mind out, but they can also work on their assignments while at the same time enjoying fresh air. As for students who love leisure gatherings, this student hub would be just it.